Direct-Writing of Cu Nano-Patterns with an Electron Beam. (December 2015) - Lai, Shih-En; Hong, Ying-Jhan; Chen, Yu-Ting; Kang, Yu-Ting; Chang, Pin; Yew, Tri-Rung
Abstract: We demonstrate direct electron beam writing of a nano-scale Cu pattern on a surface with a thin aqueous layer of CuSO4 solution. Electron beams are highly maneuverable down to nano-scales. Aqueous solutions facilitate a plentiful metal ion supply for practical industrial applications, which may require continued reliable writing of sophisticated patterns. A thin aqueous layer on a surface helps to confine the writing on the surface. For this demonstration, liquid sample holder (K-kit) for transmission electron microscope (TEM) was employed to form a sealed space in a TEM. The aqueous CuSO4 solution inside the sample holder was allowed to partially dry until a uniform thin layer was left on the surface. The electron beam thus reduced Cu ions in the solution to form the desired patterns. Furthermore, the influence of e-beam exposure time and CuSO4(aq) concentration on the Cu reduction was studied in this work. Two growth stages of Cu were shown in the plot of Cu thickness versus e-beam exposure time. The measured Cu reduction rate was found to be proportional to the CuSO4(aq) concentration.